Facilitating â€œPaguyuban Batik Tulis Langensariâ€ In Determining Targets To Respond The Global Fashion Trends - Seliari, Tutun (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2019)
Paguyuban Batik Tulis Langensari (PBTLS) is a community of batik artisans in the area around Embung Langensari, Yogyakarta. Determining the target of enthusiast of handmade batik from PBTLS crafters requires a strategy so that batik results can be right on target. The strategy that will be carried out requires an agreement that becomes a joint agreement in the community, given the current fashion trends that are developing very fast. Along with the development of the main trends in life, namely go green that returns to nature, fashion trends are also following. Today's global fashion trends are shifting from fast fashion to slow fashion. The target of the PBTLS is to determine the meeting point between products that have been produced as supply and market needs/demand. The method used in determining PBTLS targets is carried out through 4 stages. The first stage identifies the range of products that have been produced by PBTLS. The second stage determines the target users of PBTLS products. The third stage determines the direction of product development. Then the fourth step determines the uniqueness of PBTLS products. In carrying out these four steps, a crafter's poll was conducted through a "mentimeter application" conducted on 17 PBTLS artisans and focus group discussions (FGD). Through the application of the "mentimeter" the results of the PBTLS artisans poll can be immediately known to be discussed and formulated together through the FGD. The results obtained by the main target of PBTLS are middle-aged mothers consumers. Uniform fashion / formal batik fashion becomes the main target for the direction of PBTLS product development by developing the unique PBTLS products namely motifs and colors of handmade batik.